Effectiveness of A Combination of Ergonomic Exercise Therapy and Deep Breathing Relaxation to Reduce Muscle Pain (Myalgia) in Unskilled Workers (Dock Laborers) in Bima Port, Bima City in 2018 - Kurniadi Kurniadi; Ana Triana Wulandari; Julhana Julhana (Health Notions, 2018)
Myalgia was a muscle pain associated with overused muscles, get excessive load, and muscle injury due to sports or daily activities. According to WHO, patients with Myalgia in Indonesia reach 81% of the population, only 24% go to the doctor, while 71% tend to consume over-the-counter painkillers. The purpose of this study was to determine the effectiveness of a combination of ergonomic exercise therapy and deep breathing relaxation to decrease muscle pain (myalgia) in unskilled workers (dock laborers) in Bima Dock. The research was Quasy Experimental design. The sample of this study are dock laborers and found 44 people as samples. The analysis in this study was univariate and bivariate analysis with 95% confidence interval or p value of 